Depressive symptoms and degree of resilience during stomatological internship in Peru - Yuri Alejandro Castro Rodríguez (Editorial Ciencias Médicas, 2022)
Introduction: The main objective of the dental internship is to allow the student to make contact with a hospital environment. However, some problems are reported that demotivate and oversaturate students. Objective: Determine the relationship between resilience and depressive symptoms in dental interns. Methods: Cross-sectional and observational study. The sample was made up of 51 students, who were in the hospital insternishp in Lima, Peru (November 2019). The self-assessment scale for depression (10 items, Likert responses with a score from 1 to 4) and the resilience scale (14 items, Likert responses with a score from 1 to 7). The scores were related through the Spearman correlation; while the Odds ratio was used to estimate the association between the presence of depression, high resilience and sex. Results: The mean score for depressive symptoms was 21.62 ± 2.55, higher in men (22.52 ± 2.27). No correlation was found between depressive symptom scores and resilience (p = 0.082). Males were at increased risk of depressive symptoms (OR=2.14395% CI: 1.065-4.313). No significant association was found in the presence of high resilience and sex (p = 0.087). Conclusions: 40% of the interns presented depressive symptoms, being more frequent in men, while 80% presented high resilience, more frequent in women. No correlation was found between depressive symptom scores and resilience.